Population structure and shell dimension of the invasive veined whelk (Rapana venosa) - Kasapoğlu, Nazlı (Journal of Fisheries, 2021)
The veined whelk (Rapana venosa) is a widely known invasive species in the Black Sea. This species exerts negative impacts on the Black Sea ecosystem including destruction of bivalve, mussel and oyster populations. This study aimed to examine population structure using the length-frequency distribution and shell dimensions of R. venosa, collected from the Black Sea. A total of 506 specimens were collected from the Trabzon Coast and classified into 6 age groups using the Bhattacharya method. The Von-Bertalanffy growth parameters were calculated as L∞ = 10.29 cm, k = 0.09, t0 = 1.25 yr–1. The mortality and exploitation rates were estimated as total mortality Z = 0.51 yr–1, fishing mortality F = 0.31 yr–1, annual mortality M = 0.20 yr–1 and exploitation rate E = 0.60 yr–1. This study will help understanding the growth of R. venosa and its management.